Pen, print and communication in the eighteenth century - Archer-Parré, Caroline 1961-; Dick, Malcolm 19XX- (Eighteenth Century Worlds LUP Ser., 2020)
This volume considers writing and printing in parallel: it highlights the intersections between the two methods of communication; considers how writing and printing were deployed in the construction of personal and cultural identities; and explores the production, distribution and consumption of private and public letters, words and texts during the eighteenth-century.